Revisit our epistemology - Nordin, Munif Zariruddin Fikri (New Straits Times, 2016)
THERE are some 45 public and private universities in our country.The programmes offered in the universities cover various academic areas from the hard sciences such as chemistry, physics and biology to social sciences particularly economics, geography and political science, and the humanities, for example history, linguistics and Islamic studies.